ANALISIS REUSE INTENTION PELANGGAN TOUR DAN TRAVEL “X” - Karya, Denis Fidita (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aims to examine the effect of service quality and satisfaction on reuse intention on tour and travel. The research used primary data derived from the questionnaire respondents of tour and travel “X” consumer. The sample in this study amounted to 134 respondents. This study using a non-probability sampling method with a purposive sampling approach and the method used in analyzing data in this study using partial least square. The empirical result of the study show that service quality had a positive effect and significant to customer satisfaction, satisfaction had a positive effect and significant to reuse intention and service quality had a positive effect and significant to reuse intention.